Factors affecting the utilization of mental health services among undergraduate students in a Nigerian University - Olasumbo Kukoyi; Edidiong Orok; Funmilayo Oluwafemi; Tunrayo Oluwadare; Olawale Oni; Toba Bamitale; Boluwaji Jaiyesimi; Tolulope Ojo; Hannah Eze (Heliyon, 2022)
Under-utilization of mental health services among university students is a major public health concern. This study assessed the factors affecting the utilization of mental health services among undergraduate students.This research was a cross-sectional survey carried out among students of Afe Babalola University, Ado-Ekiti, Nigeria. A semi-structured self-administered questionnaire was used for data collection and multi-stage sampling technique was used in sampling the participants. Utilization, attitude, and health seeking behavior were categorized into good (≥50% score), and poor (<50% score), while social support was categorized into poor (8–18), moderate (19–25), and strong (26–32). Chi-square test and Logistic regression were used to assess the relationship between the categorical variables.450 students enrolled in this study of which 52.4% were females and mean age of 19.40 ± 1.65 years. Most students showed a good attitude (87.5%), health seeking behavior (67.8%), and poor social support (69.4%) towards mental health services. There was an association between source of information (p = 0.005), health seeking behavior (p = 0.001) and utilization of mental health services. There was also a higher likelihood for students of female gender (OR: 1.621 (1.072–2.452)) and being aged above 20 years (OR: 1.331 (0.822–2.153)) to have good utilization of mental health services.Majority of the students showed good attitude and health seeking behavior towards mental health services but there was poor utilization as well as poor to moderate social support towards mental health services. Gender, age, attitude, source of information as well as health seeking behavior are important factors that can affect the utilization of mental health services among undergraduate students. Interventions targeted towards these factors should be done to ultimately improve utilization of mental health services among undergraduate students.